The couples trip : a novel - Kvensler, Ulf, 1968- (Hanover Square Press, 2023)
Agreeing to let Milena bring her boyfriend Jacob on their annual hiking trip, Anna and Henrik find their hike going terrifyingly wrong when all three of them realize that taking Jacob was a decision that could change their lives forever.